Intertemporal Price Competition - Eaton, Jonathan; Engers, Maxim (Econometrica, 1990)
Alternating price competition between firms selling differentiated products to nonhomogeneous consumers can yield two different types of equilibria. One, which we call "disciplined, " arises when products are close substitutes. Another, which we call "spontaneous, " emerges when products are more differentiated. In disciplined equilibria, an implicit threat to cut price further, in response to an initial price cut, supports quite collusive outcomes, which become less collusive as product differentiation increases. In spontaneous equilibria, no such threat is needed. Consumers in the smaller market tend to pay a higher price, as do consumers served by the more efficient firm. Copyright 1990 by The Econometric Society.